2011
DOI: 10.1136/bjsm.2010.081299
|View full text |Cite
|
Sign up to set email alerts
|

Defining asymptomatic status following sports concussion: fact or fallacy?

Abstract: The current management of sports concussion involves a return to the baseline 'asymptomatic' status prior to returning to play and training. Unfortunately, although the term 'asymptomatic' is widely used it has not been operationally defined. This review identifies the need to formally define the term 'asymptomatic' as used in sports concussion, discusses some of the challenges associated with its definition and offers some possible solutions for further debate. The operational definition of the term 'asymptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 106 publications
1
39
0
Order By: Relevance
“…However, it is clear that some athletes, and non-athletes will report symptoms commonly used to assess concussion when they have not suffered head injury 18. This study showed that normal high school students had a preinjury baseline symptom score of 19.75 of a total possible 22.…”
Section: Discussionmentioning
confidence: 72%
“…However, it is clear that some athletes, and non-athletes will report symptoms commonly used to assess concussion when they have not suffered head injury 18. This study showed that normal high school students had a preinjury baseline symptom score of 19.75 of a total possible 22.…”
Section: Discussionmentioning
confidence: 72%
“…41 Several authors have also recently highlighted the feasibility of being able to precisely determine when a patient has truly become "asymptomatic." [42][43][44] A major source of the challenge is that postconcussion-like symptoms are nonspecific. They occur often in healthy people and are affected by daily stress.…”
Section: Practical Challenges To Implementing Restmentioning
confidence: 99%
“…Although, the focus in this review is the role of education and change in culture as it relates to prevention of concussions in youth sport, it is important to recognize that societal attitudes and sport culture has implications for all children and adolescents who participate in various sports (3,(43)(44)(45)(46)(47)(48)(49)(50). In contemporary American society, participation in sports by children and adolescents is considered a rite of passage.…”
Section: The Youth Sport Culturementioning
confidence: 99%